Letter (copy) : Shoes for Spanish refugees - Bell, Ernest A.
032-0036-001 International. FAB/AT/1017. 19th June, 1939. Mr. G. Stolz, International Federation of Trade Unions, 9 avenue d'Orsay, Paris, VIIe. Dear Comrade Stolz, SHOES FOR SPANISH REFUGEES With reference to your letter of the 16th instant regarding the consignment of shoes which have been sent from this country for the Spanish refugees in the South of France, I am attaching hereto a list (A), which gives particulars of the consignment sent by the C.W.S. "Progress" on 31st May last. Although we have made repeated application to the National Union of Boot and Shoe Operatives, these are all the particulars we have been able to procure, and I hope that they will be sufficient to enable you to go ahead with the immediate distribution of the goods. I am also sending you herewith information (list B) regarding the latest consignment forwarded by the C.W.S. "Progress" from Liverpool last week. Yours sincerely, International Dept. Enc. Two lists. 292/946/32/36